The Papers and Writings of Abraham Lincoln $1 (BVolume 1: 1832-1843s - Lincoln, Abraham, 1809-1865; Choate, Joseph Hodges, 1832-1917; Roosevelt, Theodore, 1858-1919; Schurz, Carl, 1829-1906; Lapsley, Arthur Brooks (Salt Lake City, UT : Project Gutenberg, 2004)
"The Papers and Writings of Abraham Lincoln $1 (BVolume 1: 1832-1843" by Abraham Lincoln is a historical collection edited by Arthur Brooks Lapsley, created in the early 20th century. This volume compiles significant texts and speeches from Lincoln during a crucial period of his political development, emphasizing his early views on democracy, human nature, and the pressing issue of slavery. The writings provide insight into Lincoln's character as a statesman and reflect the tumultuous socio-political landscape of his time. The opening of this volume presents an introduction by Theodore Roosevelt, which highlights Lincoln's profound understanding of leadership and morality in the face of national crises. Roosevelt discusses a speech Lincoln gave after his re-election amid civil unrest, illustrating his deep commitment to union and reconciliation rather than vengeance. This initial segment also touches on the key themes in Lincoln's political philosophy, including his unwavering belief in the potential for human self-improvement and the necessity of studying history to guide contemporary governance. Additionally, Carl Schurz's essay further explores the complexities of Lincoln$1 (Bs character, affirming his rise from humble beginnings to become a principled leader during one of America's greatest challenges. Overall, the beginning sets the stage for a rich exploration of Lincoln's foundational ideas and their significance for American history. (This is an automatically generated summary.)s
Release date is 2004-09-30
Produced by David Widger
Keywords: Lincoln, Abraham, 1809-1865; United States -- Politics and government -- 1837-1841; Lincoln, Abraham, 1809-1865 -- Correspondence; United States -- Politics and government -- 1829-1837; United States -- Politics and government -- 1841-1845